HOUSEHOLD WASTE MANAGEMENT - Apriyani, Apriyani; Rinta, Claudya; Harwidian Maharisma, Iwan (HEARTY, 2024)
The waste problem is an environmental problem in society. Waste is a problem faced by people living in East Kalimantan Province. Based on data from the Ministry of Environment and Forestry in 2022, the source of waste based on the highest type of waste in East Kalimantan Province is household waste, which amounts to as much as 55.97%. This study aimed to determine the community mechanism for household waste management using the 3R method and to analyse the availability of adequate trash bins in Loa Ulung Village, Tenggarong Seberang District. The research conducted was qualitative research with a phenomenological approach. The data analysis method used in this research is source triangulation analysis, which connects the interviews with all informants and draws conclusions from the research. This study found that the community sorted waste before disposing of it in temporary shelters. Efforts to reduce, reuse, and recycle waste have also been made, and infrastructure for waste management, such as trash cans, is available in each house. However, there are still people who burn their waste after sorting. In this study, the community mechanism for managing household waste using the 3R method has been carried out. Still, its application has yet to be maximised, and improvement and support from the government are needed.